Genetic polymorphisms of 22 autosomal STR loci in Chinese Han population. (December 2015) - Li, J.N.; Luo, H.B.; Song, F.; Hou, Y.P.
Abstract: Microreader™ 23sp ID system was a new STR multiplex system developed for forensic application, but there was a lack of population data in the Chinese Han population. This kit contained 21 non-CODIS STR loci (D6S477, D18S535, D19S253, D15S659, D11S2368, D20S470, D1S1656, D22-GATA198B05, D7S3048, D8S1132, D4S2366, D21S1270, D13S325, D9S925, D3S3045, D14S608, D10S1435, D12S391, D2S1338, D17S1290, D5S2500), one CODIS STR locus (D16S539) and the amelogenin locus. In this study, a population sample in Chengdu Han population was analyzed with the kit. Forensic genetic parameters and probability values of the Hardy–Weinberg equilibrium (HWE) were calculated with software PowerStats v1.2 and Arlequin v3.5. Allele frequencies of the 22 STR loci and further forensic genetic parameters were obtained. The results suggested that Microreader™ 23sp ID system can provide informative polymorphic data for identification and parentage testing in Chinese Han population.